Prognostic Impact of Extracapsular Lymph Node Invasion and Myofibroblastic Activity in Extrahepatic Bile Duct Cancer - Tadashi Yoshizawa; Keinosuke Ishido; Kensuke Saito; Toshihiro Haga; Hiroko Seino; Yunyan Wu; Satoko Morohashi; Kenichi Hakamada; Hiroshi Kijima (SAGE Publishing, 2017)
Extrahepatic bile duct carcinoma is a potentially malignant gastrointestinal lesion. Cancer cells spread via the lymphatic system to regional lymph nodes and help in tumor progression. However, there are no reports on the prognostic impact of extracapsular lymph node invasion and myofibroblastic activity in this cancer. Hence, we classified the histopathologic patterns of lymph nodes into 2 patterns: extracapsular lymph node invasion or not. Based on this, we investigated 32 cases of extrahepatic bile duct cancer with lymph node metastasis and classified 21 cases as positive and 11 cases as negative. The extracapsular lymph node invasion cases were associated with poor disease-free survival and overall survival. The myofibroblast density of the metastatic foci was significantly higher in the extracapsular lymph node invasion cases. This is the first study to demonstrate that extracapsular lymph node invasion cases were associated with poor prognosis and that the myofibroblast distribution contributed to malignancy.